Subjective Wearing Experience of Lehfilcon A Among Satisfied Comfilcon A Toric Lens Wearers - Mashouf J; Wan K; Hall B (Clinical Ophthalmology)
Jay Mashouf,1 Keith Wan,1 Brad Hall2 1Scripps Optometric Group, San Diego, CA, USA; 2Sengi, Penniac, NB, CanadaCorrespondence: Jay Mashouf, Scripps Optometric Group, 10549 Scripps Poway Pkwy, Ste. G, San Diego, CA, 92131, USA, Tel +1-858-530-2800, Email jaymashouf@gmail.comPurpose: To evaluate the subjective wearing experience of lehfilcon A toric lenses among subjects who were already satisfied with their comfilcon A toric lenses.Methods: This was an open-label, single arm study of currently satisfied comfilcon A soft toric contact lens (Biofinity Toric, CooperVision, Pleasanton, CA) wearers that were refit with lehfilcon A soft toric lenses (Total30® for Astigmatism; Alcon Vision LLC, Fort Worth, TX). Subjects were administered a questionnaire about satisfaction with comfort, visual performance, end of day comfort, and ease of handling with lehfilcon A toric lenses.Results: A total of 40 subjects completed the study. After one month of wear the median and interquartile range (IQR) was 8 (2) for overall satisfaction with lehfilcon A comfort, 8 (1.25) for visual performance, 7 (3.25) for end of day comfort, 9 (2) for ease of handling, and finally 8 (2) for overall satisfaction.Conclusion: A high proportion of subjects were satisfied with the subjective wearing experience with lehfilcon A toric lenses, including satisfaction with comfort, visual performance, end of day comfort, and ease of handling.Plain Language Summary: There are many different types of contact lens materials and replacement schedules for patients to suit individual needs. Despite the diversity of options, contact lens dropout continues to be high, likely influenced by discomfort and poor vision. A new frequent replacement toric contact lens is available that may offer good subjective comfort for patients. However, there is minimal data on the performance of this lens. The purpose of this study was to evaluate the subjective wearing experience with the new contact lens among patients who were already satisfied with their current toric contact lenses. The results of this study suggest that a high proportion of patients were satisfied with the subjective wearing experience with the new toric contact lens, including satisfaction with comfort, visual performance, end of day comfort, and ease of handling.Keywords: comfort, toric, contact lens, lehfilcon A, Total30 for Astigmatism